2003
DOI: 10.1101/gad.272503
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Net regulates the angiogenic switch

Abstract: Angiogenesis is fundamental to physiological and pathological processes. Despite intensive efforts, little is known about the intracellular circuits that regulate angiogenesis. The transcription factor Net is activated by phosphorylation induced by Ras, an indirect regulator of angiogenesis. Net is expressed at sites of vasculogenesis and angiogenesis during early mouse development, suggesting that it could have a role in blood vessel formation. We show here that down-regulation of Net inhibits angiogenesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 73 publications
6
82
0
1
Order By: Relevance
“…It can, in particular, induce the VEGF. We have previously shown that Net is an indirect activator of VEGF, and that inhibition of Net in an in vivo model of tumorigenicity leads to inhibition of tumour growth, impaired angiogenesis and persistence of large hypoxic regions (Zheng et al, 2003). Our results suggest that the Net-HIF-1a pathway, discovered in the current study, could be involved in these processes.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It can, in particular, induce the VEGF. We have previously shown that Net is an indirect activator of VEGF, and that inhibition of Net in an in vivo model of tumorigenicity leads to inhibition of tumour growth, impaired angiogenesis and persistence of large hypoxic regions (Zheng et al, 2003). Our results suggest that the Net-HIF-1a pathway, discovered in the current study, could be involved in these processes.…”
Section: Discussionsupporting
confidence: 69%
“…Net is involved in various physiological processes, including angiogenesis. Net regulates cell migration through repression of PAI-1 , and is required for tumour growth in xenographs (Zheng et al, 2003). Mice that express mutant Net lacking its DNA binding domain exhibit respiratory distress (Ayadi et al, 2001), and delayed wound healing due to impaired angiogenesis (Zheng et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ELK3 is activated by mitogen-activated protein kinase (MAPK)-associated pathways, such as the Ras/extracellular signal-regulated kinase (ERK) and p38 pathways, and it plays an important role in various physiological processes, including cell migration, invasion, wound healing, angiogenesis and tumorigenesis, via the regulation of c-fos, early growth response protein 1 (egr-1), and plasminogen activator inhibitor-1 (PAI-1) (19)(20)(21)(22)(23). Mutations in ELK3 disrupt vasculogenesis, angiogenesis and wound healing in mice during development and in adulthood (24,25). In addition, our previous study demonstrated that ELK3 contributes to epithelial-mesenchymal transition (EMT) of mouse hepatocytes by regulating egr-1 (26).…”
Section: Elk3 Promotes the Migration And Invasion Of Liver Cancer Stementioning
confidence: 99%
“…Recently, members of the TCF family of SRF cofactors have been characterized by knock-out studies. Elk-1 deficient mice display normal immune responses and mildly impaired neuronal gene inactivation (44) and Net mutants show defects in cell migration (45), vasculature development (46), and impaired angiogenesis during wound healing (47). The strongest phenotype with regard to immune functions is observed in SAP-1-null mice where thymocyte development is severely impaired and a decrease in the amount of CD4 ϩ and CD8 ϩ single positive (SP) cells is seen resulting from defective thymocyte positive selection (48).…”
mentioning
confidence: 99%